Detection of Co-inheritance of Hb Hope and Hb Constant Spring in Three Thai Samples by Capillary Electrophoresis - Sitthichai Panyasai (2018)
© 2015, Indian Society of Haematology & Transfusion Medicine. The diagnosis of co-inheritance of Hb Hope [β136(H14)Gly → Asp, GGT > GAT] and Hb constant spring [Hb CS; α142, Term → Gln (TAA > CAA IN α2)] by high performance liquid chromatography (HPLC) is difficult because Hb Hope has a HPLC elution pattern similar to that of Hb Pyrgos, Hb New York, Hb Kodaira, and Hb Phimai. Moreover, the Hb CS mRNA, as well as the gene product, are unstable and present at a low level in peripheral blood. We report the use of a capillary electrophoresis (CE) for diagnosis of co-inheritance of Hb Hope and Hb CS in 3 Thai females who had mild anemia with Hb and Hct varying from 91–114 g/L to 0.28–0.36 L/L, respectively. Hb Hope eluted with a retention time of 125–140 s (Zone 10) of CE electrophoregram. Furthermore, the peak of Hb CS at the retention time of 245–250 s (Zone 2) was observed in these samples. In addition, the manual analysis by taking the non-black area under both peaks of HbA and Hb Hope (inverted V) into account provided the corrected Hb CS levels which are useful in screening of heterozygote or homozygote for Hb CS. Thus, the CE method provides an accurate diagnosis of Hb Hope and Hb CS which is useful in genetic counseling, prevention and control programs for these hemoglobinopathies.